Compliance with consuming blood supplement tablets can reduce the incidence of anemia in young women in Bengkulu City - Yanniarti, Sri; Nurhaliza, Siska; Baska, Dwie Yunita; Widiyanti, Desi; Savitri, Wewet (Alma Ata University Press, 2023)
Background: Anemia is a public health problem throughout the world, globally the highest prevalence of anemia is in the Southeast Asia region at 46.6%, while in Indonesia it is 31.2%. Objectives: The aim of the study was to determine the relationship between adherence to blood supplement consumption and the incidence of anemia in young women in Bengkulu City.Methods: The research uses a cross sectional approach. The sample was calculated using the Slovin formula, obtaining a minimum sample of 160 people. The independent variable is compliance with blood supplement tablet consumption, the dependent variable is the incidence of anemia, while the confounding variables in this research are knowledge, attitudes, perceptions and peer support. Data collection on hemoglobin levels used easy touch GCHb while data on compliance, knowledge, attitudes, perceptions and peer support used a questionnaire. All data obtained were tested for univariate, bivariate and multivariate analysis using the Chi Square test and Logistic RegressionResults: The results of research using univariate analysis tests showed that respondents were anemic (14%) and respondents were not anemic (86%). Respondents did not comply with taking blood supplement tablets (27.5%) respondents complied (72.5%). The results of the bivariate analysis test were that there was a significant relationship between compliance and the incidence of anemia in adolescent girls (p value 0.000 < 0.05). There is no relationship between knowledge, attitudes, perceptions and the incidence of anemia, and there is a significant relationship between peer support and the incidence of anemia as well as the results of the multivariate analysis test, namely the most influential variable is Compliance with PR value (119.214).Conclusions: Conclusions and research suggestions show a relationship between adherence to consuming blood supplement tablets and the incidence of anemia in adolescent girls, so support from parents, health professionals, teachers and peers, as well as increased knowledge of the importance of adolescent girls consuming iron supplements are needed to increase compliance. taking blood enhancing tablets